Peran Kegiatan Kursus Pembina Pramuka Mahir Tingkat Dasar (KMD) dalam membentuk karakter generasi muda - Qaedi Zihni, Faris Hazmi; Suyahman (Jurnal Pendidikan Kewarganegaraan dan Politik, 2023)
This research aims to determine the role of the Basic Level Scout Training Course (KMD) in shaping the character of Indonesia's young generation. Using a qualitative approach and literature study, this research highlights that KMD is not just a technical scouting course, but is also a concrete vehicle for the holistic character formation of participants. KMD integrates human values, unity, deliberation and social justice through various activities such as ceremonies, discussions and community service. The research results show that KMD is able to produce a young generation who is not only proficient in the field of scouting, but also ready to face various challenges in the future. In this context, research proposes increasing the integration of character values in KMD material as well as increasing aspects of personal guidance to ensure holistic growth. The ultimate goal of KMD is to produce scout leaders who are open to input, active in outdoor learning and coaching, work cohesively in groups, and have a positive orientation in all activities.